Automatic drain rubbish collector / Muhammad Farhan Azlan - Azlan, Muhammad Farhan (2023)
Drain is one of the important systems for waterflow to prevent from flash flood happen. But some drainage does not have it because of waste thrown that make the drain clogged. In order to overcome the problem, machine was design to trap and collect all the rubbish automatically. The problem occur that makes me want to do this project is that worker did not stay at the drain all of the time to collect the rubbish because they have their own fixed time to collect it which can cause some rubbish will be missed. Therefore, morphological and Pugh chart approaches was used to finalize the design of machine. Then, the finalize design will be analyzed to ensure that the machine could collect all the rubbish automatically. It can be concluded that, this project would be success when the machine able to collect rubbish in the drain automatically